Dermatological clinical atlas of rheumatic diseases with skin manifestations and differential diagnoses in patients treated at the Cassiano Antônio Moraes University Hospital from 2020 to 2022 (Brazilian Journal of Health Research, 2023)
Introduction:Skin tissue reactions to external agents are translated by morphological responses of limited number, which constitute elementary lesions. Through its combination, morphological signs appear that characterize syndromes or diseases. Elementary lesions are classified into five well-defined groups: color changes, edematous elevations, solid formations, liquid collections, thickness changes, losses and reparations. Several rheumatic diseases may present with cutaneous manifestations, such as collagenoses, myopathies, systemic vasculitis and inflammatory arthropathies. In addition, it is important to remember other etiologies such as infection, pharmacoderma and neoplasms. Objectives: To develop a dermatological clinical atlas of patients with rheumatic diseases and their differential diagnoses that presented cutaneous manifestations. Methods: Data obtained from medical records were collected and photographs authorized by patients treated during the period 2020 to 2022 were collected at the Cassiano Antônio de Moraes University Hospital (HUCAM), of the Federal University of Espírito Santo (UFES). Conclusion: In this context, the present clinical atlas contributes to the adequate recognition of elementary lesions, especially in cases of rheumatologic diseases and their differential diagnoses. Thus, it is possible to expand medical knowledge for the early identification and appropriate treatment of these clinical conditions.
Keywords: Elementary lesions; Rheumatic diseases; Skin manifestations